Kineobactrum sediminis gen. nov., sp. nov., isolated from marine sediment. Issue 8 (30th May 2019) - Chang, Ya-Qi; Meng, Xue; Du, Zhao-Zhong; Du, Zong-Jun
Abstract : A novel Gram-stain-negative, rod-shaped marine bacterium, designated strain F02 T, was isolated from a marine saltern in Weihai, PR China. The cells of strain F02 T were approximately 0.8–1.0×3.0–4.0 µm and motile by means of a polar flagellum. Strain F02 T grew optimally at 33–35 °C, pH 7.5 and in the presence of 3.0 % (w/v) NaCl. Strain F02 T showed oxidase- and catalase-positive activities. Phylogenetic analysis of 16S rRNA gene sequences revealed that strain F02 T belonged to the family Halieaceae and exhibited 16S rRNA gene sequence similarities of 96.6 and 96.4 % to the type strains of Chromatocurvus halotolerans and Parahaliea mediterranea, respectively. The major cellular fatty acids of strain F02 T were C18 : 1 ω7 c, C16 : 1 ω7 c, C15 : 0 and C18 : 1 ω9 c . The major polar lipids of strain F02 T were phosphatidylglycerol, phosphatidylethanolamine and one unidentified aminolipid. Strain F02 T contained Q-8 as the sole respiratory quinone. The genomic DNA G+C content was 58.4 mol%. The genome sequences of strain F02 T and Chromatocurvus halotolerans DSM 23344 T had an OrthoANI value of 70.5 %, and the average amino acid identity value between the two genomes was 62.6 %. The sequence similarity value between the rpoB genes of strain F02 T and Chromatocurvus halotolerans DSM 23344 T was 79.5 %. On the basis of polyphasic analysis, strain F02 T represents a novel species in a new genus, for which the name Kineobactrum sediminis gen. nov., sp. nov. is proposed. The type strain is F02 T (=KCTC 52616 T =MCCC 1H00224 T ).